Concurrent binding to DNA and RNA facilitates the pluripotency reprogramming activity of Sox2. Issue 7 (4th February 2020) - Hou, Linlin; Wei, Yuanjie; Lin, Yingying; Wang, Xiwei; Lai, Yiwei; Yin, Menghui; Chen, Yanpu; Guo, Xiangpeng; Wu, Senbin; Zhu, Yindi; Yuan, Jie; Tariq, Muqddas; et al.
Abstract: Some transcription factors that specifically bind double-stranded DNA appear to also function as RNA-binding proteins. Here, we demonstrate that the transcription factor Sox2 is able to directly bind RNA in vitro as well as in mouse and human cells. Sox2 targets RNA via a 60-amino-acid RNA binding motif (RBM) positioned C-terminally of the DNA binding high mobility group (HMG) box. Sox2 can associate with RNA and DNA simultaneously to form ternary RNA/Sox2/DNA complexes. Deletion of the RBM does not affect selection of target genes but mitigates binding to pluripotency related transcripts, switches exon usage and impairs the reprogramming of somatic cells to a pluripotent state. Our findings designate Sox2 as a multi-functional factor that associates with RNA whilst binding to cognate DNA sequences, suggesting that it may co-transcriptionally regulate RNA metabolism during somatic cell reprogramming.